DETERMINATION OF DARK MATTER TYPE BY X-RAY SOURCES STATISTICS - Tugay, A.V. (Одеські астрономічні публікації, 2014)
The current cosmological model includes cold dark matter, which consists of massive nonrelativistic particles. There are also some observational and theoretical evidences for warm dark matter. The existence of warm DM can be examined by measuring of the galaxy clusters density profiles and accurate counting of dwarf galaxies. In this work I suppose that DM haloes are well traced by X-ray gas in clusters, groups, pairs and even single galaxies. The type of DM is inspected with the Xgal sample of 5021 X-ray emitting galaxies observed by XMM-Newton. The selection bias of this sample is also analyzed.